2017
DOI: 10.1080/17474124.2017.1327347
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia and colorectal cancer surveillance in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) patients are at an increased risk of developing colorectal cancer (CRC), a devastating complication of which intestinal dysplasia is the precursor. Considerable progress has been made to determine CRC risk in IBD, identification & management of dysplasia and preventative methods. Traditionally, surveillance colonoscopies with random colonic biopsies was used. However recent data suggests that chromoendoscopy is a better method of surveillance. Using 5-aminosalicylic acid agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 89 publications
1
11
0
1
Order By: Relevance
“…Through screening, it was found that the detection rate of CRC in urban residents was 0.23%, and the detection rate of advanced adenoma was 1.27%, which is at a low level, lower than the previously reported 0.25 and 3.07% (21). The detection rate in males was higher than in females, which is consistent with the characteristics of CRC incidence in males higher than females (22). With the increase of age, the detection rate of advanced neoplasms, non-advanced adenomas, and any neoplasms increased both for males and females, suggesting that CRC screening is more effective in the elderly population (23).…”
Section: Discussionsupporting
confidence: 68%
“…Through screening, it was found that the detection rate of CRC in urban residents was 0.23%, and the detection rate of advanced adenoma was 1.27%, which is at a low level, lower than the previously reported 0.25 and 3.07% (21). The detection rate in males was higher than in females, which is consistent with the characteristics of CRC incidence in males higher than females (22). With the increase of age, the detection rate of advanced neoplasms, non-advanced adenomas, and any neoplasms increased both for males and females, suggesting that CRC screening is more effective in the elderly population (23).…”
Section: Discussionsupporting
confidence: 68%
“…Colon carcinoma is the second most commonly diagnosed cancer. The majority (60-85%) of CRC is classified as sporadic cancers and around 10-30% is familial or hereditary, stressing the importance of environmental and microbial factors in tumorigenesis [ 108 , 109 ]. IBD accounts for 1-2% of CRC cases, but the cancer risk in UC patients is 5 times higher than the general population and colitis-associated CRC is more aggressive [ 110 ].…”
Section: Microbiota Dybiosis and Mucosal Biofilms In Colon Cancersmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gut that includes ulcerative colitis (UC) and Crohn's disease (CD) [1]. While the incidence of IBD only occurs in 1-2% of all colorectal cancer (CRC) patients in the general population [2], this incidence has been quantified to increase up to 5% in patients suffering over 20 years of the disease [3]. The risk of CRC development rises in patients with IBD and is a more belligerent carcinoma with an earlier age of onset than sporadic CRC [2]; with the major driving force of carcinogenesis being inflammation and immunosuppression [4].…”
Section: Introductionmentioning
confidence: 99%
“…While the incidence of IBD only occurs in 1-2% of all colorectal cancer (CRC) patients in the general population [2], this incidence has been quantified to increase up to 5% in patients suffering over 20 years of the disease [3]. The risk of CRC development rises in patients with IBD and is a more belligerent carcinoma with an earlier age of onset than sporadic CRC [2]; with the major driving force of carcinogenesis being inflammation and immunosuppression [4]. This has led to a poor prognosis for patients with IBD, with 1 in 6 patients dying from cancer [5].…”
Section: Introductionmentioning
confidence: 99%